The Order for the administration of the Lord's Supper or Holy Communion - Philippine Episcopal Church. Liturgy and Ritual ([Sagada?, 1962)
Approved for trial use by the Bishop of the Philippines, April 2, 1962
Keywords: Phil. Epis. Church -- liturgy and ritual; Eucharist. I. Title